Genotypic characterization of vibrio parahaemolyticus from seafood and river water in Kuching-Samarahan District, Sarawak - Ng, Lee Tze (Universiti Malaysia Sarawak (UNIMAS), 2007)
The presence of Vibrio parahaemolyticus in marketed seafood and surface water samples in Kuching-Samarahan District, Sarawak were examined over 6 months period (December 2003 to May 2004). During the sampling period, a total of 81 marketed seafood samples and 114 surface water samples were collected. Based on morphological, biochemical and genotype identification, 50% of the marketed seafood samples and 62% of the surface water samples were positive for V. parahaemolyticus, yielding 69 and 87 isolates respectively. High occurrence of V. parahaemolyticus was observed in both the marketed seafood and surface water samples. Out of 69 confirmed V. parahaemolyticus isolates, 34 isolates from marketed seafood and another 49 isolates from surface water samples (out of 87 isolates) were selected for further analysis) Their antibiotic resistance, presence of plasmid(s), DNA fingerprinting using RAPD-PCR (Randomly Amplified Polymorphic DNA), and ERIC-PCR (Enterobacterial Repetitive Intergenic Consensus sequence or ERIC), and the presence of virulence genes <thermostabile direct hemolysin gene, tdh, and TDH-related hemolysin gene, trh) were investigated. Based on the ERIC primer, DNA sequencing was performed on 12 of the selected isolates. All the V. parahaemolyticus isolates showed different resistancy towards twelve antimicrobial agents tested. The Multiple Antibiotic Resistance (MAR) index calculated ranged from 0.50 to 0.92. The isolates were differentiated into 20 patterns through plasmid profiling, with plasmid sizes ranging from 3.1 to 63.0 kb. Results revealed that there is no clear correlation between the plasmid profiles and the antibiotic resistance patterns. RAPD and ERIC-PCR analysis successfully subtyped all the 83 isolates. RAPD and ERIC clustering analysis managed to differentiate the isolates into different clusters in which the isolates were distributed based on the month of sampling. Based on the Simpson's index of diversity, results from both RAPD and ERIC methods were almost similar, 99.05% and 99.00%, respectively. Virulence genes detection via specific PCR showed that only 10.8% of the isolates were positive for trh gene, whereas no isolate was positive for the tdh gene. The presence of trh gene in this organism indicates potential risk towards public health in event of an outbreak.